Associations of single versus multiple anthropometric failure with mortality in children under 5 years: A prospective cohort study. (December 2021) - Gausman, Jewel; Kim, Rockli; Subramanian, S.V.
Abstract: Background/objectives: Stunting, underweight, and wasting are used to monitor nutritional status in children, but they do not identify children with concurrent anthropometric failures (AF). Our study estimates the association between AF and mortality in children with single versus multiple failures, then calculates the percentage of child deaths attributable to AF. Subjects/methods: Using data from a prospective, longitudinal study of 3605 children from age 1 to age 5 years in Ethiopia and India, we estimate the association between AF and mortality using conventional definitions (stunting, underweight, and wasting) and the mutually exclusive categories of stunted only underweight only, wasted only, stunted and underweight (SU), underweight and wasted, and stunted, underweight, and wasted (SUW), adjusting for socioeconomic status and other demographic variables. Last, we calculate the population attributable fraction. Results: Children who were SU and SUW had 3.20 (95% CI: 1.69, 6.06; p < 0.001) and 5.52 (95% CI: 2.25, 13.56; p < 0.001) times the odds of death in fully adjusted models by Round 2 compared to children with no failure, while no increased mortality risk was found among children with other categories of failure. We estimate that 42.69% of child deaths can be attributed to children who are SUW (17.02%) or SU (25.67%), accounting for nearly 80% of child deaths from AF. Conclusions: This study provides new insight to programs and policy to better identify children most at risk of malnutrition-related mortality. Highlights: Children with multiple anthropometric failures have a greater risk of all-cause mortality. Our study uses prospective, longitudinal data that adjusts for socioeconomic status. Our results provide new insight to identify children most at risk of death due to growth faltering.